Hubungan Positive Emotion, Workplace Spirituality dengan Flourishing pada Wanita Karir - Ratu Haya Aulia Nabilla; Agus Salim (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The phenomenon of social problems that arise due to the increasing interest of career women cannot be denied because discrimination against women in the world of work still occurs today, such as remuneration rights, health benefits, leave rights, and even sexual harassment. The aim is to find out whether there is a relationship between positive emotions, workplace spirituality and flourishing in career women. The population of career women is 959,631 people with research subjects of 274 career women in the Special Region of Yogyakarta who are working, either unmarried or married (including unmarried or already having children) with an age range of 19-40 years and a minimum education of high school / vocational high school or equivalent collected through google form. This research method uses non-experimental quantitative with a correlational approach. Data analysis uses validity and reliability tests, classical assumption tests (normality, linearity, and multicollinearity), multiple linear regression analysis tests, and effective contribution tests. The results of the study showed a significant relationship between positive emotions, workplace spirituality and flourishing in career women; there is a significant relationship between positive emotions and flourishing in career women and; there is a significant relationship between workplace spirituality and flourishing in career women.